KEBIJAKAN KELAUTAN DALAM RANGKA MENJAGA DAN MENGELOLA SUMBER DAYA ALAM LAUT SEBAGAI UPAYA MEWUJUDKAN INDONESIA SEBAGAI POROS MARITIM DUNIA - Hanim, Lathifah; Noorman, Mohammad Shofii Noorman (Faculty of Law, University of Muhammadiyah Malang, 2017)
Indonesia has a vision World Maritime Poros. The government's agenda corresponds with the vision include the construction of a maritime culture, maritime resource management, infrastructure development and connectivity maritime, maritime security and defense diplomacy. Marine resources has great potential for the development of the national economy in order to realize Indonesia as the shaft maritime world, however, the setting and its use should be undertaken with caution in order to avoid destruction of the population, habitat and ecosystem. As a developing country, Indonesia must establish closer cooperation with technologically advanced countries to explore the marine resources. In addition, to realize the ideals of Indonesia as the World Maritime shaft must be able to ensure that safety and security in the sea area a top priority.